The relationship between home and school variables and students' religious development in NCR secondary schools - Santos, Bienvenido V. (Animo Repository, 1994)
This study explores the effectiveness of secondary Catholic schools in influencing the religious development of students based on seven outcome measures.It pursued the findings of Flynn (1985) that (1) school variables rather than home factors have the primary influences in most of the outcome measures, and that (2) schools can make the difference regardless of the students' home background.The respondents were fourth year students. Three hundred thirty-five of them were from 10 top-performing Catholic schools while 185 were from five of the better known public schools in the National Capital Region. The students were made to reflect on their lives through a 205-item survey-questionnaire.As a descriptive-comparative-correlational investigation, this study employed multiple correlation through stepwise regression. This was done in order to determine the separate and collective contributions which a number of predictor variables made in each outcome measure. It also used multi-variate procedures to find out significant statistical differences between the Catholic schools and the public schools. It also detected whether school differences existed among the 10 Catholic school on all six predictor variables and seven outcome variables of religious development.The major findings at .05 level of significance were as follows:1. Catholic schools scored significantly higher than the public schools on the students' home environment and school social climate variables 2. Catholic schools also scored significantly higher in the outcomes measures of religious knowledge, moral values, and attitudes towards the Church 3. There were significant correlations between school differences among the 10 Catholic schools on all the school-related variables, and on all the outcome measures of religious development 4. There were significant positive correlations between the home and the school variables and the outcome measures of religious development and,5. School variables, rather than home environment, had more pervading influences on the students' religious development. In particular, the quality of school life variable recurrently appeared as a significant influence in almost all of the outcome measures.Conclusions drawn from the study were, that the values of a religious group could be effectively taught in a religiously-oriented educational system regardless of the level of parental religiousness. Second, Catholic schools could claim school effectiveness only to a moderate extent because the public school sample scored almost as well in religious practice, justice values, religious commitment and personal faith. Finally, there were clear indications of an alarming level of alienation among the young regarding moral values and the teaching authority of the Church.